Observed Changes in Extreme Temperature and Precipitation Indices on the Qinghai-Tibet Plateau, 1960–2016 - Gong, Xiangwen; Wang, Xuyang; Li, Yuqiang; Ma, Lei; Li, Manyi; Si, Hongtao (Frontiers in Environmental Science, 2022)
The Qinghai-Tibet Plateau (QTP), also known as the Earth’s “third pole,” is sensitive to climate change due to its extensive areas at high elevation, which are presently dominated by snow and ice. Based on daily observations from 1960 to 2016 at 94 meteorological stations, we quantified and compared changes in climate extremes on China’s QTP using 16 extreme temperature indices and 11 extreme precipitation indices, which calculated using colder (1961–1990) and warmer (1988–2016) base periods, respectively. The study showed that when a warmer base period is used, the trend magnitude of the cold temperature indices is amplified, while the trend magnitude of the warm temperature indices and the percentile-based precipitation indices are diminished. The regionally averaged temperature index trends were consistent with global warming, namely warmth indices such as the number of warm days, warm nights, summer days, and tropical nights all showed significant increases. However, the cold indices, such as the number of cool days, cool nights, ice days, and frost days, decreased significantly. The number of frost days and ice days decreased the fastest (3.9 and 2.9 days/decade, respectively), while the length of the growing season increased the fastest (2.9 days/decade). The warming trend strengthened with increasing latitude, and the occurrences of daytime extreme temperature events increased with increasing longitude. In addition, cold temperature events increased in frequency and intensity at high elevations, while warm temperature events decreased. We also found that average monthly maximum 1-day precipitation and maximum consecutive 5-day precipitation increased by 0.1 and 0.3 mm per decade, respectively. Extreme precipitation occurrences were more common in places with low latitudes and high longitudes. The strengthening Subtropical High Area (SHA) and Subtropical High Intensity (SHI), Westward movement of Subtropical High Western Ridge Point (SHW) have contributed to the changes in climate extremes on the Qinghai-Tibet Plateau. The study’s findings will provide a more comprehensive reference for predicting the occurrence of extreme events and improving the region’s disaster prevention capability.